The Effect of Green Supply Chain Management Practices on Sustainability Performance - Febry Anindya Hanumsari; Yuli Liestyana; Yekti Utami (Universitas Tidar, 2021)
Sustainability performance as measured through environmental, economic, and social performance, could be a competitive advantage for organizations amid the current tight business competition. Green Supply Chain Management (GSCM) practices which consist of green purchasing, green manufacturing, green marketing, green distribution and packaging, internal environmental management, environmental education, and investment recovery, could be a way for organizations to obtain their sustainability performance. This study aims to examine the impact of GSCM on sustainability performance of natural-dyed batik SME in Yogyakarta Province. The data were collected using questionnaire and later obtained 39 respondents who were selected by using area sampling technique. The data were analyzed descriptively and quantitively using Partial Least Square (PLS) with SmartPLS 3.2.8 software. The results of the analysis show that green purchasing, green manufacturing, green marketing, internal environmental management, and environmental education affect SME’s environmental, economic, and social performance positively and significantly. On the other hand, green distribution and packaging as well as investment recovery do not have positive and significant impact on SME’s environmental, economic, and social performance. The conclusion of this study is that the adoption of GSCM practices does not affect the overall SME’s sustainability performance, yet affects individually.